PERLINDUNGAN HUKUM HAK DESAIN INDUSTRI GENSET YANG PRODUKNYA TELAH DIPUBLIKASIKAN DI NEGARA LAIN DITINJAU DARI UU DESAIN INDUSTRI - Rogomos Simamora; Simona Bustani (Faculty of Law, Universitas Trisakti, 2023)
Industrial Design is one form of IPR. However, there are still many disputes on applications for registration of industrial designs. The question What is the legal protection of industrial design rights holders of generators marketed in Indonesia according to the Industrial Design Law? and How is the analysis of the decision of the judge Central Jakarta Commercial Court regarding the generator industrial design dispute based on the Industrial Design Law? The research method is in the form of normative law with an analytical descriptive nature. Using primary data in the form of interviews to support secondary data. Qualitatively analyzed by drawing deductive conclusions. In conclusion, the legal protection of generator industry design rights holders marketed in Indonesia according to the Industrial Design Law is still inadequate and ineffective because it does not impose automatic substantive examinations related to novelty aspects and based on the author's analysis, the judgment is not in accordance with the provisions of the Industrial Design Law because the Plaintiff is not an interested party to cancel the industrial design based on the license to authorize. It should be Chongqing Longli Power Equipment Co., Ltd as the owner of industrial design in China.